2011
DOI: 10.1016/j.febslet.2011.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination of mRNA cycling sequence binding protein from Leishmania donovani (LdCSBP) modulates the RNA endonuclease activity of its Smr domain

Abstract: Edited by Michael IbbaKeywords: CCCH Zn-finger mRNA turnover Smr domain RNA endonuclease Ubiquitination Leishmania donovani a b s t r a c tIn trypanosomatid parasites, an octanucleotide sequence (C/A)AUAGAA(G/A) in the UTRs primarily determines the stability of S-phase specific mRNAs. A multi-domain protein LdCSBP from Leishmania donovani interacts with the UTR of an S-phase RNA containing the octanucleotide sequence through its unique CCCH-type Zn-finger motifs. Interestingly, the RNA binding protein contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…2 B and C), which is consistent with the DNA endonuclease activity observed in other SMR-containing proteins (20)(21)(22)(23)(24)(25)(26). In addition, our results showed that the SMR domain of SOT1 has RNA endonuclease activity (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…2 B and C), which is consistent with the DNA endonuclease activity observed in other SMR-containing proteins (20)(21)(22)(23)(24)(25)(26). In addition, our results showed that the SMR domain of SOT1 has RNA endonuclease activity (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies demonstrated the SMR domain exhibits DNA nicking nuclease activity in vitro (20)(21)(22)(23)(24)(25). Furthermore, a C-terminal SMR domain in Leishmania donovani S-phase mRNA cycling sequence binding protein (CSBP) has RNA cleavage activity in vitro (26). These findings suggest that the SMR domain has nuclease activity.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…RBPs can be modified at the post-translational level by phosphorylation [69], ubiquitination [10,11] and poly(ADP-ribosyl)ation (PARylation) [12] to achieve temporal/spatial-specific post-transcriptional control of gene expression. PARylation is performed by Poly(ADP-ribose) polymerases (PARPs), which utilize NAD to synthesize poly(ADP-ribose) polymer (pADPr) with the resulting sizes varying from 2 to 200 ADP-ribose units [13,14] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%